Experimental and theoretical study of dephasing processes in the kinetics of photoexcited carriers in GaN. Issue 3 (20th March 2014) - Garrett, Gregory A.; Shishehchi, Sara; Rudin, Sergey; Malinovsky, Vladimir; Wraback, Michael; Bellotti, Enrico
Abstract: The scattering and dephasing processes that accompany the initial photoexcitation of electron‐hole pairs in the semiconductor GaN are studied by sub‐picosecond time‐resolved photoluminescence. The rise time of the carrier recombination at the band edge after excitation 750 meV above the band gap is analyzed as a function of initial photoexcited carrier density and sample temperature. To elucidate the findings, simulations were performed based on a two band model with a non‐parabolic conduction band and using a generalized Monte‐Carlo technique. Results showed a small dependence in the rise time on the initial carrier density but a strong dependence on the sample temperature, where simulation and experiment scaled proportionately. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)